17B-hydroxysteroid dehydrogenases as acyl thioester metabolizing enzymes. (1st June 2019) - Hiltunen, J. Kalervo; Kastaniotis, Alexander J.; Autio, Kaija J.; Jiang, Guangyu; Chen, Zhijun; Glumoff, Tuomo
Abstract: 17β-Hydroxysteroid dehydrogenases (HSD17B) catalyze the oxidation/reduction of 17β-hydroxy/keto group in position C17 in C18- and C19 steroids. Most HSD17Bs are also catalytically active with substrates other than steroids. A subset of these enzymes is able to process thioesters of carboxylic acids. This group of enzymes includes HSD17B4, HSD17B8, HSD17B10 and HSD17B12, which execute reactions in intermediary metabolism, participating in peroxisomal β-oxidation of fatty acids, mitochondrial oxidation of 3R-hydroxyacyl-groups, breakdown of isoleucine and fatty acid chain elongation in endoplasmic reticulum. Divergent substrate acceptance capabilities exemplify acquirement of catalytic site adaptiveness during evolution. As an additional common feature these HSD17Bs are multifunctional enzymes that arose either via gene fusions (HSD17B4) or are incorporated as subunits into multifunctional protein complexes (HSD17B8 and HSD17B10). Crystal structures of HSD17B4, HSD17B8 and HSD17B10 give insight into their structure-function relationships. Thus far, deficiencies of HSD17B4 and HSD17B10 have been assigned to inborn errors in humans, underlining their significance as enzymes of metabolism. Highlights: Several HSD17Bs display functional diversity and are multitasking. At least HSD17B4, 8, 10 and 12 accept acyl-thioester (CoA or ACP) substrates. Involved metabolic processes include both breakdown and synthetic pathways. Crystal structures of HSD17B4, 8 and 10 give into insights their functions.